Business Model Canvas: Stingless Bee Honey / Nur Faizah Roslan - Roslan, Nur Faizah (2020)
Key activities for my business are stingless bee honey stand. This functional product helps the customer to be more efficient. This product is worth to invest in since it can prevent pest attacks to the stingless bee honey because if there are the enemy of the beehive, it capable of invading the colony. Hence, it can avoid stingless bee honey breeder loss